Pollution Control and Clean up technics of contaminated Aquifers - ΚΑΛΛΕΡΓΗΣ Γ. Α. (Bulletin of the Geological Society of Greece, 2002)
The vulnerability of aquifers against external pollution,is estimated with the use of lithofasic, hydrologie and geochemical criteria and GIS technics. When pollution prevention is not feasible, its control should include containment measures against farther spread of pollutants such as installation of physical and hydraulic barriers in combination with extraction of polluted water. Based on the nature and the source of the pollution, several technics have been developed, which are discussed in the present paper. The most efficient for clean up of the saturated zone is the pump and treat technic